Analytic Approach for 2D Phased Array Delay Law Calculation in Case of Inspection of Objects with Complex Geometry - Fyleris, Tautvydas; Jasiuniene, Elena (Elektronika ir Elektrotechnika, 2019)
Objects with complex geometry need to be inspected quickly and reliably, therefore it is not practical to use fixed focus transducer, because of wave propagation effects. To mitigate the problem with the irregular shape, it is possible to use a phased array with applied delay laws. For calculating required delays, it is required to have an object model with known surface points and have an algorithm which calculates. This paper presents computing friendly analytic method which could be used in the case when the object model is given by lines or it is possible to calculate surface tangents. In this paper is assumed that geometry is approximated with B-splines. Results of the algorithm are verified with finite element method. DOI: 10.5755/j01.eie.25.2.23200